DEVELOPMENT OF MOTORCYCLE TUNE UP TUTORIAL VIDEO MEDIA FOR GRADE X STUDENTS OF MOTORCYCLE TECHNIQUE AND BUSINESS EXPERTISE COMPETENCY AT SMK MUHAMMADIYAH BAWANG - Budiyanto; Ariwibowo, Bayu; Mahendra, Sena; Burhan, Nurul (Jurnal Pendidikan Teknik Mesin, 2025)
This study aims to develop learning media in the form of a video tutorial on motorcycle tune-up practices for class X students of Motorcycle Engineering and Business Expertise at SMK Muhammadiyah Bawang. The method used is research and development (R&D) by adapting the Borg & Gall model to the final product trial stage. Data collection was carried out through observation, interviews, expert validation questionnaires, student response questionnaires, and practical skills tests. The results of the study showed that the video tutorial media developed obtained the category "feasible" to "very feasible" from the material and media aspects, and received a positive response from students. The use of video tutorials has proven effective in improving students' understanding of concepts and practical skills, as well as supporting student-based learning approaches. This study contributes to the development of digital-based learning media in vocational education environments.